Manfaat Teknologi Smartphone dalam kegiatan Pembelajaran Pendidikan Islam Di Masa Pandemi Corona-19 - Rachmadonna Shinta Daulay; Hidayah Pulungan; Adelia Noviana; Siti Hurhaliza (Yayasan Rahmat Islamiyah, 2020)
With technological that are do fast and rapid, people are flocking to the flow of world development that requiresthem to become increasingly sophisticated and easy, one pf which is to use gadgets. In today’s digital era,technology is aprimary need that must be met to help and facilitate humans in all fields. People who do not understand technology are required to learn and use it is not considered an obsolete person. Nowadays, one of the main trends in tecnhnology is gadgets, such as cell phones,tablets, laptops, cameras, etc. As if the gadgets is food for everyone from all walks of life, men and women, big and small, young and old. Gadgets are tools to facilitate all human needs and activities, so they are popular and become the choice of variorus groups, including students at this time, such as to access information. Add insight, as a lifestayle, and self-exstence. Like friends, because gadgets have applications and updates from day to day that are loved by many people and make life even more intants. Many students use gadgets at school, such as Android phone, laptops and the like because it undeniable that theirpresence is very helpful and benefical for them, one of them is in the learning process. Especially at this time that is experience covid 19 school children can get to school as usual. From this corona virus we cannot do teaching and learning activities face to face or at school, because this virus is very fast spread through humans. Of course this online learning is very useful for breaking the chain or corona virus spread. This is very useful for the loyalty of student and teachres, helping the government in overcoming and guarding against spreading to relatives so the smartphone technology is very useful for the loyalty of students and teachers, helping the government in overcoming against spearding to relatives. So the smartphone technology is very useful for a student because it relly helps the learning through technology